Contractual Penalty for Monetary Obligations - Bitrakov, Andrej; Zahrastnik, Kristjan (65 pravne znanosti v Mariboru, 2026)
The Slovenian Obligations Code expressly provides that a contractual penalty may not be stipulated for monetary obligations. The rationale behind this prohibition rests on the view that default interest already fulfils the function of sanctioning delays in the performance of monetary obligations, while simultaneously incentivising the debtor to perform in a timely manner. With a view to assessing the adequacy of this legal framework, the authors begin by conducting a detailed analysis of the legal institute of the contractual penalty within Slovenian law of obligations. This is followed by a critical examination of the prevailing positions in legal doctrine and case law, which reject the admissibility of contractual penalties in cases involving the non-performance of monetary obligations. In conclusion, the authors reflect on whether the absolute prohibition of contractual penalties for monetary obligations is truly consistent with the principles of contemporary contract law.